THE COMMUNICATION STRATEGY OF IBLIS IN THE PERSPECTIVE OF MARKETING COMMUNICATION: A NARRATIVE ANALYSIS OF Q.S. AL-A‘RĀF [7]: 20–21 AND Q.S. ṬĀHĀ [20]: 120 - Syarifuddin, Syarifuddin (Sekolah Tinggi Agama Islam Sadra, 2026)
This study is motivated by the increasing tendency of contemporary marketing communication practices to prioritize persuasion over honesty, thereby raising ethical concerns within the promotional mix. In this context, the narrative of Satan’s temptation of Prophet Adam in Sūrah Al-A‘rāf and Sūrah Ṭāhā is considered relevant as an early representation of morally deviant persuasive communication patterns. This study aims to identify the forms of persuasive communication embedded in the narrative and to analyze their relevance to promotional mix practices from the perspective of Islamic marketing ethics. Methodologically, this study employs a qualitative approach within a hermeneutic paradigm, utilizing thematic (mawḍū‘ī) content analysis. The analysis is further strengthened by Virginia Wilson’s content analysis framework and an approach to Qur’anic textual analysis. The primary data consist of Qur’anic verses related to the story of Adam and Satan, supported by exegetical literature and contemporary marketing references as conceptual comparisons. The findings indicate that Satan’s communication pattern reflects manipulative persuasive strategies, including the use of emotional appeals, the construction of misleading value claims, and subtle persuasive influences aligned with soft-selling characteristics. These patterns correspond to unethical practices across various elements of the promotional mix, including advertising, sales promotion, public relations, and interpersonal communication. This study concludes that such communication patterns contradict the fundamental principles of Islamic marketing, which emphasize honesty, transparency, and accountability. Therefore, strengthening the ethical dimension in promotional practices is essential to ensure sustainability and to build trust in modern marketing activities.